Efficacy of Febuxostat for the Prevention of Progression of Chronic Kidney Disease in Hyperuricemia patients - Usman Ashraf, Azhar Ali Khan, Maryam Javed, Rana Muhammad Umar, Sehrish Sarwar, Hafiz Hamad Ashraf (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hyperuricemia has been linked with adverse outcomes in chronic kidney disease. Urate lowering drugs are recommended for treating hyperuricemia in CKD patients. Aim: To determine efficacy of Febuxostat for the prevention of progression of chronic kidney disease in hyperuricemia patient. Study design: Descriptive case series Setting: Nephrology Department of Sheikh Zaid Hospital Lahore. Sample size 200 patients fulfilling the inclusion criteria were included. Serum urate and creatinine levels (to estimate eGFR) were assessed and patients were started on 40mg to 120mg once daily dose of febuxostat tablet, for a period of 12 weeks. The efficacy of the treatment was assessed after 12 weeks. Result: Total 200 patients were included. The patient mean age was 36.2±9.251, mean eGFR was 36.3±11.79, mean serum urate levels were 8.65±1.134 and mean dose of febuxostat was 70.2±27.1. 71.5% were males and 28.5% females. Febuxostat was efficacious in 28.5% of the patients. The data was stratified by age, gender, febuxostat dose, and kidney disease severity. Post - stratification chi square test was1applied. It was seen that there was no significant relationship of efficacy with age. Gender and dose of febuxostat (P value of >0.05). Conclusion: Febuxostat is effective in reducing the progression of chronic kidney disease in hyperuricemic patients. Keywords: Hyperuricemia, Chronic Kidney Disease, Urate Lowering Drugs, Febuxostat